THE SPEECH OF THE SURFER: A STUDY IN THE SOCIAL IMAGINARY (Fiep Bulletin - online, 2014)
This article had the objective to make an analysis of the practical one of surf, identifying the directions of the adventure, risk and vertigo. The half-structuralized interview was used, where if it searched to identify in the speech of the surfer the social imaginary. The analyzed group demonstrated simplicity, and proved clearly the objective of the practical one, or either, to slide the most perfect waves, being the vertigo disclosed at this moment. The thought always is focus in this objective, the risks is calculated, but never the certainty in the success of the onslaught is had, of this form if becoming the adventure of the practical of surf.
Keywords: Surfe; imaginary; speech